Science, technology and innovation for socioeconomic development : Towards vision 1441 : proceedings of the 14th IAS conference ..., organised in Kuala Lumpur, Malaysia, 21-24 Mar., 2005 - IAS Conference on Science, Technology and Innovation for Socioeconomic Development 2005 : Kuala Lumpur, Malaysia); Ergin, MehmetZou bi, Mouneef R; Zou bi, Mouneef R.; Islamic World Academy of Sciences (Jordan : Islamic World Academy of Sciences, 2008)
Sience; Islamic countries; economic development; congresses
Includes bibliographical referencesSience; Islamic countries; economic development; congresses
Keywords: Science -- Islamic countries -- Congresses; Economic development -- Islamic countries -- Congresses